2019
DOI: 10.4054/demres.2019.40.35
|View full text |Cite
|
Sign up to set email alerts
|

Family arrangements and children’s educational outcomes: Heterogeneous penalties in upper-secondary school

Abstract: BACKGROUND This paper studies whether new family patterns fostered inequality of educational opportunities in upper-secondary education in Italy. OBJECTIVE To analyse the association between children's educational outcomes and a wide range of family arrangements, including the time of exposure to marriage (never married, married before or after the birth). Empirical analyses also consider whether these demographic characteristics of the origin family more strongly affect children from more or less well-off fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
1
14
0
1
Order By: Relevance
“…Institutional and societal factors that vary across countries and periods could underlie the somewhat mixed findings. 28,29,108,109 For instance, utilizing data from the 1970 British Cohort study, two studies found that the negative associations between divorce and adolescents' academic achievement among youth with highly educated parents were driven by the loss of access to fathers' financial resources. 28,29 However, as noted by the authors, few non-resident fathers paid child support during this period in Britain.…”
Section: Compensatory Class or Floor Effect?mentioning
confidence: 99%
“…Institutional and societal factors that vary across countries and periods could underlie the somewhat mixed findings. 28,29,108,109 For instance, utilizing data from the 1970 British Cohort study, two studies found that the negative associations between divorce and adolescents' academic achievement among youth with highly educated parents were driven by the loss of access to fathers' financial resources. 28,29 However, as noted by the authors, few non-resident fathers paid child support during this period in Britain.…”
Section: Compensatory Class or Floor Effect?mentioning
confidence: 99%
“…The highest growth rate of personnel costs is in the field of electricity, gas, steam -by 17.6%, in the field of mining operations -by 14.9%, in the field of real estate operations -by 13.9%, in administrative support activity -by 12%, in the production sector -by 12%, in the wholesale and retail trade -by 10.8%. 6. Sixth, on the basis of Eurostat data, we found that the difference between the maximum level of personnel costs in the field of electricity, gas, steam, the highest value of which is noted in Austria is 117.3 thousand euros and the minimum in the area of accommodation and services catering in Bulgaria -3.9 thousand euros, is 30 times.…”
Section: Discussionmentioning
confidence: 83%
“…The influence of the family on the acquisition of education is of paramount importance. A tremendous conclusion about this was made by Italian scientists Guetto r., Panikella N., who write that "children living in singleparent or two cohabitant households of biological parents have worse educational outcomes than children of two married biological parents", We agree with the authors that" children of highly educated parents are subject to more severe penalties if they consider access to the most prestigious academic program" [6].…”
Section: Literature Reviewmentioning
confidence: 88%
“…However, whereas some studies did find that socioeconomically advantaged families manage to shelter their pupils from the consequences of parental break-up (Amato & Anthony, 2014;Grätz, 2014), others found stronger penalties amongst highly-educated families (Bernardi & Boertien, 2016Bernardi & Radl, 2014;Brand et al, 2019). More recently, Bernardi and Comolli (2019) and Guetto and Panichella (2019) suggested that heterogeneity in divorce penalty depends on the combination between social background and the educational outcome considered: the smallest penalty will be observed for very rare-e.g. tertiary education attainment for children of disadvantaged families-and very common outcomes-e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 99%